RANCANG BANGUN MODUL PERCOBAAN COUNTER DAN BINARY ADDER CIRCUIT DI LABORATORIUM ELEKTRONIKA DIGITAL - Rasidin, Eka Handika; Ch, Syafarudin; Wiryajati, I Ketut (Depertment of Electrical Engineering University of Mataram, 2025)
This study develops an experimental module for Counter and Binary Adder Circuit practicals to enhance Electrical Engineering students' understanding of logic circuits at the University of Mataram. The Counter circuit, a sequential circuit triggered by a clock signal, includes synchronous and asynchronous types. The Binary Adder Circuit performs binary addition. The module incorporates key components such as JK and D flip-flops, logic gates (AND, OR, XOR, NOT), a shift register, and a full adder. Design and testing confirm proper functionality. The Counter module operates correctly with LED indicators, and the Binary Adder produces accurate binary calculations. This module effectively supports practical learning in logic circuitsThis study develops an experimental module for Counter and Binary Adder Circuit practicals to enhance Electrical Engineering students' understanding of logic circuits at the University of Mataram. The Counter circuit, a sequential circuit triggered by a clock signal, includes synchronous and asynchronous types. The Binary Adder Circuit performs binary addition. The module incorporates key components such as JK and D flip-flops, logic gates (AND, OR, XOR, NOT), a shift register, and a full adder. Design and testing confirm proper functionality. The Counter module operates correctly with LED indicators, and the Binary Adder produces accurate binary calculations. This module effectively supports practical learning in logic circuits